An Analysis of Tea Farmers' Income: A Case Study of the Sekar Aji Farmer Group - Nova Widi Setyo Nugroho; Nur Andriyani; Muslim Afandi (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the factors influencing the income of tea farmers in Dukuh Kayulawang, Mriyan Village, Boyolali Regency. Using a quantitative approach with multiple linear regression analysis, the research is based on primary data collected from 31 tea farmers who are members of the Sekar Aji Farmer Group. The independent variables examined include the amount of fertilizer used, land area, years of experience as a general farmer, years of experience as a tea farmer, and level of education. The results of the analysis reveal that general farming experience and education level have a significant positive effect on tea farmers’ income. In contrast, the amount of fertilizer, land area, and years of experience as a tea farmer do not show a significant influence. These findings highlight the importance of broad farming experience and education in enhancing income, and underscore the need for improved efficiency and innovation in the management of tea farming. Relevant stakeholders are encouraged to focus on capacity-building efforts to help farmers increase their productivity and income.